Strengthen research on effect of meteorological factors on injury to reduce climate-related injury burden - Wenjun MA; Jianxiong HU (环境与职业医学)
Climate change poses a significant threat to public health. Existing studies on the health impacts of climate change focus primarily on chronic and infectious diseases, with limited research on injury. To address this gap, this issue launched a special column titled "Climate change and injuries". Through interdisciplinary integration of atmospheric science and public health, we explored the impact of climate change on injury risk and burden from diverse perspectives. This initiative aims to deepen a comprehensive understanding of the impact of climate change on human health, enhance China's capacity to address climate-related health risks, reduce associated disease burden, and provide scientific evidence for targeted adaptation measures.